DETERMINAN STRUKTUR MODAL DAN DAMPAKNYA TERHADAP NILAI PERUSAHAAN - Mega, Ayu Indira; Suarjaya, Anak Agung Gede (E-Jurnal Manajemen, 2014)
The purpose of firm to maximizing firm value can be influence by capital structure decision. This research focus on capital structure determinant and the impact to the firm value in property and real estate sector. Purposive sampling used as sampling technique, and 28 firms took as sample. Analyzed data using path analysis with regression models. This study found that assets structure related significant with capital structure and profitability associated significant with firm value. In capital structure decision suggested to attention on asset structure and to maximize firm value the firm to concern about profitability, that because this two variable has significant influence. Keywords:firm value, capital structure determinant